Safety in numbers : pointers for a global safety culture at work (Geneva, 2003)
"Hazardous substances kill 340.000 workers annually. Asbestos alone claims about 100.000 lives. Cancer is the biggest cause of work-related diseases, responsible for 32% of fatalities ... "